The responses of tropical forest species to global climate change: acclimate, adapt, migrate, or go extinct? - Brian Machovina; Evan M Rehm; Kenneth J Feeley (Frontiers of Biogeography)
In the face of ongoing and future climate change, species must acclimate, adapt or shift their geographic distributions (i.e., "migrate") in order to avoid habitat loss and eventual extinction. Perhaps nowhere are the challenges posed by climate change more poignant and daunting than in tropical forests, which harbor the majority of Earth’s species and are facing especially rapid rates of climate change relative to current spatial or temporal variability. Due to the rapid changes in climate predicted for the tropics, coupled with the apparently low capacities of tropical tree species to either acclimate or adapt to sustained changes in environmental conditions, it is believed that the greatest hope for avoiding the loss of biodiversity in tropical forest is species migrations. This is supported by the fact that topical forests responded to historic changes in climate (e.g., post glacial warming) through distributional shifts. However, a great deal of uncertainty remains as to if tropical plant and tree species can migrate, and if so, if they can migrate at the rates required to keep pace with accelerating changes in multiple climatic factors in conjunction with ongoing deforestation and other anthropogenic disturbances. In order to resolve this uncertainty, as will be required to predict, and eventually mitigate, the impacts of global climate change on tropical and global biodiversity, more basic data is required on the distributions and ecologies of tens of thousands of plants species in combination with more directed studies and large-scale experimental manipulations.